Digital trends in education (Docentes 2.0 Journal, 2019)
Technological development was accentuated at the end of the 20th century, a process driven by ICT advances, understood as the set of technologies for acquisition, production, storage, treatment, communication, registration and presentation of information, in the form of voice , images and data contained in signals of an acoustic, optical or electro-magnetic nature. They include electronics as the base technology for the development of telecommunications, information technology and audiovisual.
Keywords: Digital trends; education